Epidemiological Assessment of ovarian cancer in some northern Iraqi provinces - Nadia Youhana Ibrahim; Samira Abdul-Hussain Abdulla (Tikrit Journal of Pure Science, 2022)
Introduction: Ovarian cancer is the third most common malignancy and the second most common cause of cancer death worldwide among gynecologic cancers.